Developing a serious game for gaze stability rehabilitation in children with vestibular hypofunction - José Ortega Solís; Pierre Reynard; Karen Spruyt; Cécile Bécaud; Eugen Ionescu; Hung Thai-Van (Journal of NeuroEngineering and Rehabilitation, 2023)
Abstract Background Children with vestibular hypofunction (VH) may have gaze instability, balance disorders, and delayed postural-motor development. Gaze stabilization exercises (GSE) are designed to improve dynamic visual acuity (DVA). We aimed to assess the acceptability of a serious game prototype called Kid Gaze Rehab (KGR) designed to implement GSE training in children with VH, combined with traditional vestibular rehabilitation. Effects on DVA and motor performance were also analyzed. Methods Twelve children (6 to 9 years old) were included. Sessions were held at the hospital twice a week, for 5 weeks. An adapted French version of The Child Simulator Sickness Questionnaire (SSQ) and the Face Scale Pain-Revised (FPS-R) were used to assess pain in the cervical region and undesirable side effects after each session. Vestibular and motor function parameters (active and passive DVA and Movement Assessment Battery for Children–Second Edition, MABC-2) were assessed before and after the training. Results All children included completed the 10 sessions. The FPS-R visual analog scale and SSQ showed good cervical tolerance and no oculomotor or vegetative adverse effects nor spatial disorientation. After training, active DVA scores were significantly improved for the right, left, and up directions (p < 0.05). Passive DVA scores were significantly improved for the left and down directions (p < 0.01 and p < 0.05, respectively). MABC-2 scores were improved in the balance and ball skill sections (p < 0.05). Conclusion An innovative pediatric training method, the use of a dedicated serious game for gaze stabilization was well-tolerated as a complement to conventional vestibular rehabilitation in children with VH. Moreover, both DVA and motor performance were found to improve in the study sample. Although replication studies are still needed, serious game-based training in children with VH could represent a promising rehabilitation approach for years to come. Trial registration The study was conducted in accordance with the Declaration of Helsinki and approved by an Institutional Review Board (local ethics committee, CPP Sud-Est IV, ID 2013–799). The study protocol was registered on ClinicalTrials.gov (NCT04353115).